Synthesis of Silver Nanoparticles in an Eco-friendly Way using Lannea coromandelica Aqueous Bark Extract - Nuritasari Azis; Abdul Wahid Wahab; Abdul Karim; Nursiah La Nafie; Triana Febrianti (Jurnal Kimia Sains dan Aplikasi, 2022)
In this present study, silver nanoparticles (AgNPs) were synthesized through an easy, rapid, and eco-friendly pathway using Lannea coromandelica aqueous bark extract. The obtained AgNPs were characterized using Ultraviolet-Visible (UV-Vis) spectrophotometer, Fourier Transform Infrared (FTIR), X-ray Diffraction (XRD), and Scanning Electron Microscope (SEM). The results indicated that the pH of colloidal AgNPs played a vital role in forming AgNPs. The pH ranges used in this study were 6, 8, 10, and 12. The formation of AgNPs was confirmed by observing the surface plasmon resonance (SPR) band at each pH and obtaining a wavelength of 430.50, 419.50, 418.50, and 410.00 nm. A comparison of the FTIR spectra of Lannea coromandelica aqueous bark extract and AgNPs showed the contribution of the O-H group in reducing silver ions. XRD diffractogram showed that AgNPs formed at 2θ = 37.8056o (1 1 1), 44.0345o (2 0 0), 64.3942o (2 2 0), dan 77.5003o (3 1 1) with face-centered cubic (FCC) crystal structure, and the average particle size was 22.5047 nm. SEM results showed that the nanoparticles have a non-uniform and irregular shape.